STRATEGI PENGEMBANGAN USAHA PENYEWAAN DAN PENJUALAN PERALATAN KEMAH PADA TOKO F-CAMP TANAH DATAR - Beni Rawadi; Sandra Dewi (BORJUIS: JURNAL OF ECONOMY, 2025)
This research is motivated by the slow development of business in the business of renting and selling camping equipment. This is the aim of this research to analyze and determine an effective strategy for business development in the rental and sales of camping equipment run by the F-Camp shop. The method used in this research activity is a qualitative method. Based on the results of SWOT, IFE, EFE, and Weight Score analysis, it can be concluded that the strategy needed by the F-Camp store is to utilize the strengths of the company and minimize any threats that have the potential to disrupt business development at the Tanah Datar F-Camp store. . The strategies obtained based on the results of the analysis include providing a sense of comfort for consumers and increasing the ability to compete with competitors, offering products at affordable prices and expanding market reach, increasing the amount of product inventory and establishing clear sanctions for damage to rental products, Maximizing the use of media social media as promotional media and establish cooperation with nature activists